Differences of Opinion, Short-Sales Constraints, and Market Crashes - Hong, Harrison; Stein, Jeremy C. (Review of Financial Studies, 2003)
We develop a theory of market crashes based on differences of opinion among investors. Because of short-sales constraints, bearish investors do not initially participate in the market and their information is not revealed in prices. However, if other previously bullish investors bail out of the market, the originally bearish group may become the marginal “support buyers,” and more will be learned about their signals. Thus accumulated hidden information comes out during market declines. The model explains a variety of stylized facts about crashes and also makes a distinctive new prediction—that returns will be more negatively skewed conditional on high trading volume.